Implementation of the Restorative Justice Concept with the Scope of the Police Handling Criminal Cases - Mundhi, Mundhi; Gunarto, Gunarto (UNISSULA Semarang, 2024)
The purpose of this study is to determine and analyze the mechanism of the Police in using the concept of restorative justice in handling criminal cases. In this writing, the author uses a normative legal method with research specifications in the form of descriptive analysis. Within the framework of the Pancasila Legal State Concept, the restorative justice concept approach has only been implicitly recognized in the constitution and has only been partially regulated in several criminal law regulations, including the Child Criminal Justice System Law, the Special Autonomy Law for Papua Province, which has recognized the existence of a